PERMODELAN MEKNISME EMPAT BATANG PENGHUBUNG PADA MESIN PENANAM PADI DENGAN MENGGUNAKAN SOFTWARE SOLIDWORKS - - Marzuki; Samsul Bahri; - Usman (Jurnal Teknologi, 2014)
Wet rice cultivation management system and method of rice cultivation in Aceh are still done traditionally. These activities are requiring the expertise of a very high order to obtain a same pattenr of  spacing and a short time planting . Heterogeneity of plant spacing will have an impact on the seed growth and caused  the  delay of planing, the farmers would find it  difficult to do  weeding, fertilizing and spraying. This study aims to determine the design of mechanism parameters of four link bar design  for modeling mechanism in order to obtain the optimum parameters of the locus of planting. Design tools of rice growers is  using the four link bar mechanism which is able to work mechanically to take the rice seedlings from hoper and plant it with the same pattern  spacing, closing the planting hole, reducing the time of planting and of course make the  operational costs efficiently . The methods used in this research  are the design of the prototype and the design of functional and structural approaches. This research has produced a prototype component of the combined mechanisms of rice cultivation four link bar mechanism which is driven by a chain mechanism. Functional and structural testing  gave the performance planting mechanism which can move the locus of decision-continuous form of seeds and planting seeds for the six rows